Analisis Sistem Pengendalian Intern Kas Pada PT. Ira Widya Utama Medan - Putri Kemala Dewi Lubis; Adinda Ulina Barus (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2021)
This study aims to describe the application of the internal cash control system and analyze the internal control system for cash receipts and disbursements applied to PT. Ira Widya Utama in Medan, is it in accordance with the elements of the control system according to COSO. PT. Ira Widya Utama is a company engaged in construction services and housing development. The problems that arise in this study, where there is still evidence of receipt and proof of cash disbursements have not been serially numbered printed and are still contained in the supporting document records of the company's cash receipts transactions that have not been affixed with the "Paid" stamp by the cash receipts department which is feared to be re-recorded by the parties. irresponsible and will provide communication errors to customers and cashiers after the payment for the transaction. This research approach uses descriptive method to analyze the company's internal cash control system. In terms of research on the effectiveness of the company, the authors carry out data collection techniques using the interview method. Based on the results of interviews using an assessment measured by the five elements of the internal control system, it can be concluded that the internal cash control implemented by PT. Ira Widya Utama in Medan is still not in accordance with the elements of the internal control system.